SUITABILITY OF PRESCRIPTION WRITING WITH HOSPITAL FORMULARY IN HEART DISEASE PATIENTS AT CITRA HUSADA HOSPITAL - Della Utami Inayaturrahman; sutrisno; Sholihatil Hidayati (LPPM Universitas dr. Soebandi, 2024)
Introduction: The hospital formulary contains a list of drugs that have been agreed upon by the medical staff and compiled by the Therapeutic Pharmacy Team (TFT) which is determined by the hospital director. The hospital formulary serves as a quality and cost control for drugs that will facilitate rational drug selection, reduce medical costs, and optimize services to patients. Objective: This study aims to identify the suitability of standardized prescription writing with the hospital formulary. Methods: This study used a descriptive observation method with the source of medical record data for inpatients and outpatients with heart disease in October-December 2023 as many as 154 with total sampling technique. Results: The results of this study showed that the suitability of prescription writing with the hospital formulary was 98.93% and those that were not in accordance with the hospital formulary were 1.03%. Conclusion: The conclusion in this study is that almost all prescriptions for heart disease patients are in accordance with the Hospital Formulary.